The interactive effects of operators and parameters to GA performance under different problem sizes - Pabico, Jaderick P.; Albacea, Eliezer A.
The complex effect of genetic algorithm's (GA) operators and parameters to its performance has been studied extensively by researchers in the past but none studied their interactive effects while the GA is under different problem sizes. In this paper, We present the use of experimental model (1)~to investigate whether the genetic operators and their parameters interact to affect the offline performance of GA, (2)~to find what combination of genetic operators and parameter settings will provide the optimum performance for GA, and (3)~to investigate whether these operator-parameter combination is dependent on the problem size.
Keywords: Genetic algorithms; Traveling salesman problem; Experimental models; Combinatorial optimization